KONSUMSI DALAM EKONOMI ISLAM - Azwar Hamid Nasution (Institut Agama Islam Negeri Padngsidimpuan, 2017)
Consumption is an individual process to fulfill human daily needs. In Islam, it is one of primer needs which is called as maslahat. Islamic Economy manage human in completing their needs, for example the object must be halal, the way to get the object must follow the syariah and the transaction must be completed with the commandments and requirements.